Future Technology Creativity of Teachers Some Aspects of Development - Hayitov Jonibek Xolboboyevich (Genius Journals, 2022)
The article describes the essence of developing the creativity of future teachers of "Technology" in the teaching of specialty subjects.
Keywords: Technology; Science; Teacher; Creativity